2021
DOI: 10.1109/access.2021.3111083
|View full text |Cite
|
Sign up to set email alerts
|

Machine Learning Based Indoor Localization Using Wi-Fi RSSI Fingerprints: An Overview

Abstract: In the era of the Internet of Things (IoT) and Industry 4.0, the indoor usage of smart devices is expected to increase, thereby making their location information more important. Based on various practical issues related to large delays, high design cost, and limited performance, conventional localization techniques are not practical for indoor IoT applications. In recent years, many researchers have proposed a wide range of machine learning (ML)-based indoor localization approaches using Wi-Fi received signal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
41
0
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(63 citation statements)
references
References 172 publications
(184 reference statements)
0
41
0
3
Order By: Relevance
“…The interest in fingerprinting based indoor localization has received momentum recently due to the adopted potential from the field of deep learning [3]. Fingerprinting based approaches can be differentiated from the device perspective [8].…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…The interest in fingerprinting based indoor localization has received momentum recently due to the adopted potential from the field of deep learning [3]. Fingerprinting based approaches can be differentiated from the device perspective [8].…”
Section: Related Workmentioning
confidence: 99%
“…In that regard, fingerprinting based indoor localization represents an attractive solution for large-scale pedestrian localization [3]. In an offline-phase radio fingerprints detectable in the environment are collected at known reference positions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some of them are more general [12][13][14] and differ from each other mainly for the review's procedure. Others analyze in more detail the data source, differentiating between channel state information [15] and received signal strength [16]. The literature also offers surveys on Machine Learning techniques that leverage Wi-Fi data to face human fall detection [17], human activity recognition [18], smart homes [19], motion detection [20], and human mobility [21].…”
Section: Related Workmentioning
confidence: 99%
“…The authors of [14] identified several ways to enhance the radio map, including data cleansing and denoising. In [15], the Received Signal Strength Indicator (RSSI) measurements were extracted to overcome sparsity with a stacked Denoising Au-toEncoder (DAE).…”
Section: Related Workmentioning
confidence: 99%